CONTEXTUAL ARCHITECTURE IN THE FACULTY OF ENGINEERING AND FACULTY OF ECONOMY AND BUSINESS UNIVERSITY OF INDONESIA IN DEPOK - Nursandi, Izwan Ariq; Pane, Ilham; Hibatullah, Helmi Bariq; Purwantiasning, Ari Widyati (Border: Jurnal Arsitektur, 2022)
University of Indonesia (UI) already known by public with the peculiarities of the buildings on the campus. As the development of the times, the mass of buildings on The UI in Depok is also experiencing rapid development. One of the functions of the new building which is certainly intended to support learning activities. The construction of new buildings, necessarily have an impact on the face of the UI Campus in general which has the characteristic of the traditional buildings that has been known before. In this case, the contextual architecture present in the application of the design in the newest buildings on The UI Campus. Contextual architecture itself is divided into two types, namely the harmony and contrast. This study aims to understand and identify the application of the contextual architecture of the buildings in the Engineering Faculty (FT) and Economy & Business Faculty (FEB) University of Indonesia. Methods in this research is a descriptive qualitative method with phase-analysis based on the type of harmony and contrast of those aspects are size & scale, shape, and color in the case study area. Conclusion of the result in this study that The FT and FEB University of Indonesia in Depok discovery of the balance of the architecture of the contextual building harmony and contrast.